Demand and Market Opportunities for Condensed Milk Products in Uzbekistan’s Food Industry - Mohinur Sayitniyozovna Ismattova (Zien Journals, 2025)
This article explores the demand and market opportunities for condensed milk products in Uzbekistan’s food industry. It analyzes consumer preferences, economic and cultural drivers of demand, historical consumption patterns, and the growing role of condensed milk in both domestic consumption and international trade. The study also highlights market opportunities such as product diversification, innovation, export potential, and integration with Uzbekistan’s broader food security strategy. Particular attention is given to the challenges faced by the dairy sector, including technological modernization, supply chain constraints, and the need for adherence to international quality standards. The discussion provides a comprehensive view of how condensed milk can serve as a driver of value-added growth in Uzbekistan’s agri-food sector
Keywords: Condensed milk; food industry